Pelatihan Penyusunan Kas Kecil (Petty Cash) Menggunakan Metode Imprest dan Fluktuasi untuk Meningkatkan Pembelajaran - Dedi Suhendro; Agus Perdana Windarto; Anjar Wanto (JPM: Jurnal Pengabdian Masyarakat, 2021)
Petty cash includes a number of funds specially formed for routine and relatively small expenses. Petty cash is used to mark relatively small management expenses such as purchasing office stationery, consumption funds for meeting purposes. As a person who is trusted by the leadership to manage petty cash, he must be able to organize and plan petty cash funds and make financial records that are re-booked by the company's finance department using the imprest and fluctuation methods. Many students still do not understand how and techniques to prepare petty cash using the imprest and fluctuation methods, therefore the training for preparing petty cash using the imprest and fluctuation method is very important for students of SMK Satrya Budi 2 Simalungun Regency Trade in order to face the Expertise Competency Test (UKK) and National Examination (UN) so that students can work on exam questions quickly and accurately. After participating in this training, it is hoped that the students of SMK Satrya Budi 2 Trading, Simalungun Regency can gain insight and knowledge about the methods and techniques for compiling petty cash bookkeeping, completing exam questions quickly and accurately in accordance with the allotted time. and the pass rate reaches 100%.